Ceramic plate and its manufacturing method
A ceramic plate with controlled N content and specific silicon compounds achieves improved insulation properties by controlling grain growth and reducing dielectric breakdown voltage, suitable for circuit boards in vehicles and industrial applications.
Patent Information
- Application Number
- JP2022510626
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-26
- Filing Date
- 2021-03-24
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2041-03-24
AI Technical Summary
Ceramic plates manufactured with silicon dioxide as a sintering aid often fail to exhibit expected insulation properties due to the inclusion of silicon compounds that reduce dielectric breakdown voltage.
A ceramic plate composition containing silicon nitride, YMgSi2O5, Y8Si4O14, and Y2Si3O3N4, with controlled N content below 8.0% by mass, is produced through heat treatment of a green sheet with specific silicon dioxide and oxide additives, promoting grain growth and reducing grain boundary formation.
The resulting ceramic plate achieves enhanced insulation properties with improved dielectric breakdown voltage, suitable for use in circuit boards for hybrid cars, electric cars, and industrial robots.
Smart Images

Figure 0007621336000002 
Figure 0007621336000003 
Figure 0007621336000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a ceramic plate and a method for making the same. [Background technology]
[0002] Silicon nitride is a material that has excellent strength, hardness, toughness, heat resistance, corrosion resistance, thermal shock resistance, etc., and is therefore used as a raw material for producing ceramics used in various industrial parts such as die casting machines and melting furnaces, as well as automobile parts, etc. Furthermore, ceramics containing silicon nitride also have excellent mechanical properties at high temperatures, and therefore their application to gas turbine parts, which require high-temperature strength and high-temperature creep properties, is being considered.
[0003] From the viewpoint of improving ceramic productivity, etc., a method for manufacturing ceramics by sintering raw materials containing silicon nitride and a sintering aid is known. For example, Patent Document 1 describes a method for manufacturing a silicon nitride sintered body by adding a sintering aid such as silicon dioxide to a specific silicon nitride fine powder and sintering it under a nitrogen atmosphere. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 08-048564 Summary of the Invention [Problem to be solved by the invention]
[0005] By adding silicon dioxide as a sintering aid to silicon nitride, it becomes possible to sinter at a low temperature where the grain growth rate is low, and it is possible to manufacture a more homogeneous ceramic plate. This tendency is proportional to the increase in the amount of silicon dioxide used. However, as mentioned above, the ceramic plate obtained by adding silicon dioxide as an aid may not exhibit the expected insulating properties.
[0006] An object of the present disclosure is to provide a ceramic board having excellent insulation properties and a method for manufacturing the same. [Means for solving the problem]
[0007] One aspect of the present disclosure provides a ceramic plate containing silicon nitride and YMgSi2O5N, wherein a maximum content of the YMgSi2O5N is less than 8.0 mass% based on the total amount when a quantitative composition analysis of the surface is performed by an X-ray diffraction method.
[0008] The ceramic plate has excellent insulating properties because the maximum content of the YMgSi2O5N in the surface composition is suppressed to a predetermined value or less.
[0009] The reason why the above-mentioned effects are obtained is not entirely clear, but the present inventors speculate as follows. First, when silicon dioxide, magnesium oxide, and yttrium oxide are contained as sintering aids, the obtained ceramic plate has a composition of YMgSi2O5N, Y8Si4N4O 14 and Y2Si3O3N4. And YMgSi2O5N, Y8Si4N4O 14 Among Y2Si3O3N4, the wettability of YMgSi2O5N to silicon nitride is higher than that of Y8Si4N4O 14 The wettability of YMgSi2O5N to silicon nitride is inferior to that of Y2Si3O3N4, and when YMgSi2O5N is contained in a ceramic plate, grain boundaries and the like may be formed between YMgSi2O5N and silicon nitride. The inventors speculate that the grain boundaries and the like cause a decrease in the dielectric breakdown voltage even if they are at a level that cannot be detected by electron probe microanalyzer (EPMA) analysis or scanning electron microscope (SEM) observation. In other words, the ceramic plate according to the present disclosure was invented based on a new finding that YMgSi2O5N, among the compounds generated by the use of a sintering aid, affects the decrease in the dielectric breakdown voltage.
[0010] The above ceramic plate is Y8Si4N4O 14and Y2Si3O3N4, and the above Y8Si4N4O was found by quantitative analysis of the surface composition using an X-ray diffraction method. 14 And the total content of the Y2Si3O3N4 may be less than 4.0 mass% based on the total amount.
[0011] The above ceramic plate is Y8Si4N4O 14 and Y2Si3O3N4, and the above YMgSi2O5N, the above Y8Si4N4O, and the above YMgSi2O5N, and the above Y8Si4N4O 14 and the above Y8Si4N4O relative to the total amount of the above Y2Si3O3N4 14 The ratio of the total amount of Y2Si3O3N4 may be 0.250 or more. The ceramic board manufactured using silicon dioxide may contain the above-mentioned three silicon compounds, but by reducing the proportion of YMgSi2O5N, which has a relatively low wettability with silicon nitride, the decrease in the breakdown voltage can be further suppressed.
[0012] One aspect of the present disclosure provides a method for producing a ceramic board, comprising a step of heat-treating a green sheet containing silicon nitride, silicon dioxide, magnesium oxide, and yttrium oxide, wherein the content of the silicon dioxide is 0.90 parts by mass or more based on the total amount of the green sheet, and the heat treatment is performed at a temperature rise rate of 0.50°C / min or less at 1400 to 1800°C.
[0013] The method for producing the ceramic board described above uses a sintering aid containing silicon dioxide and performs heat treatment under specific conditions, thereby making it possible to produce a ceramic board with a reduced YMgSi2O5N content. Effect of the Invention
[0014] According to the present disclosure, it is possible to provide a ceramic board having excellent insulation properties and a method for manufacturing the same. [Brief description of the drawings]
[0015] [Figure 1]FIG. 1 is an optical microscope photograph showing a portion of the surface of the ceramic plate prepared in Example 1. [Diagram 2] FIG. 2 is an optical microscope photograph showing a part of the surface of the ceramic plate prepared in Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, embodiments of the present disclosure will be described. However, the following embodiments are merely examples for explaining the present disclosure, and are not intended to limit the present disclosure to the following contents.
[0017] Unless otherwise specified, the materials exemplified in this specification can be used alone or in combination of two or more. When a plurality of substances corresponding to each component are present in the composition, the content of each component in the composition means the total amount of the plurality of substances present in the composition, unless otherwise specified. In this specification, the "steps" may be steps independent of each other or steps performed simultaneously.
[0018] One embodiment of the ceramic plate is a ceramic plate containing silicon nitride and YMgSi2O5N. The ceramic plate may vary depending on the manufacturing method, but the ceramic plate may contain, for example, Y8Si4N4O in addition to silicon nitride and YMgSi2O5N. 14 The ceramic plate may contain silicon nitride as a main component, preferably silicon nitride, YMgSi2O5N, Y8Si4N4O 14 and consists only of Y2Si3O3N4.
[0019] In the ceramic plate, silicon nitride contains β-silicon nitride as a main component. Silicon nitride may contain α-silicon nitride, but preferably consists of only β-silicon nitride. The content of β-silicon nitride in silicon nitride may be, for example, 95 mass% or more, or 98 mass% or more, or may be 100 mass% (meaning that all is β-silicon nitride). In the manufacturing process of the ceramic plate, raw material powder is sintered, so that α-silicon nitride in the raw material powder is converted to β-silicon nitride. The content of α-silicon nitride can be reduced by changing the sintering conditions, etc.
[0020] In the ceramic plate, the maximum content of the YMgSi2O5N when the composition on the surface is quantitatively analyzed by X-ray diffraction is less than 8.0 mass% based on the total amount. The maximum content of the YMgSi2O5N may be, for example, 7.9 mass% or less, 7.8 mass% or less, or 7.7 mass% or less. By setting the upper limit of the maximum content of the YMgSi2O5N within the above range, the insulation properties of the ceramic plate can be further improved. The maximum content of the YMgSi2O5N when the composition on the surface is quantitatively analyzed by X-ray diffraction is usually 7.4 mass% based on the total amount. End and may be 7.5 mass% or more, generally about 7.6 mass%. The maximum content of the YMgSi2O5N can be adjusted within the above range, and may be, for example, 7.4 mass% or more and less than 8.0 mass%, 7.4 to 7.9 mass%, 7.4 to 7.8 mass%, or 7.4 to 7.7 mass%, or 7.5 to 7.7 mass%. The total amount as a reference means the total amount of the components detected by X-ray diffraction.
[0021] The ceramic plate may be manufactured by sintering a mixture containing silicon nitride and a sintering aid including silicon dioxide. The ceramic plate may be manufactured by sintering a mixture containing silicon nitride and a sintering aid including silicon dioxide. 14 and Y2Si3O3N4.
[0022] The above Y8Si4N4O when the composition at the surface was quantitatively analyzed by X-ray diffraction method 14 The total content of Y2Si3O3N4 may be, for example, less than 4.0 mass%, 3.7 mass% or less, 3.5 mass% or less, or 3.0 mass% or less, based on the total amount. 14 And the total content of the above Y2Si3O3N4 may be, for example, 0.5 mass % or more, or 0.8 mass % or more, based on the total amount.
[0023] The above YMgSi2O5N and Y8Si4N4O were subjected to quantitative analysis of the surface composition by X-ray diffraction. 14 and the above Y8Si4N4O relative to the total amount of the above Y2Si3O3N4 14 The lower limit of the ratio of the total amount of Y2Si3O3N4 may be, for example, 0.250 or more, 0.252 or more, 0.253 or more, or 0.255 or more. By setting the lower limit of the ratio within the above range, the decrease in the dielectric breakdown voltage can be further suppressed, and the insulating properties of the ceramic board can be further improved. The upper limit of the ratio may be, for example, 0.350 or less, or 0.345 or less. The ratio can be adjusted within the above range, and may be, for example, 0.250 to 0.350, 0.253 to 0.345, or 0.255 to 0.345. The ratio can be adjusted, for example, by the amount of sintering aid used in the production of the ceramic board, the composition ratio, and the conditions of the heat treatment of the green sheet.
[0024] The above-mentioned YMgSi2O5N and Y8Si4N4O 14The respective contents of YMgSi2O5N and Y2Si3O3N4 are determined by quantitative analysis using X-ray diffraction. Specifically, the measurements are performed as follows. First, measurements are performed on 30 arbitrary regions (regions of 0.6 mm × 0.9 mm size) on both main surfaces of the ceramic plate, and the region with the maximum YMgSi2O5N content is determined from the 30 regions. The YMgSi2O5N content measured in the determined region is taken as the maximum YMgSi2O5N content. In the region giving the maximum YMgSi2O5N content, Y8Si4N4O 14 The content of each of YSi3O3N4 was measured, and the total amount was calculated as Y8Si4N4O 14 Furthermore, the total content of YMgSi2O5N, Y8Si4N4O, and Y2Si3O3N4 is calculated from the total amount of each component measured in the above region that gives the maximum content of YMgSi2O5N. 14 and the above Y8Si4N4O relative to the total amount of Y2Si3O3N4 14 and the ratio of the total amount of Y2Si3O3N4 is determined.
[0025] Quantitative analysis of the ceramic plate surface reveals that the composition is silicon nitride, YMgSi2O5N, Y8Si4N4O 14 Other components other than Y2Si3O3N4 may be contained within a range that does not impair the effects of the present invention. The other components also include impurities. The content of the other components may be, for example, 5.0 mass% or less, 3.0 mass% or less, 2.0 mass% or less, 1.0 mass% or less, 0.5 mass% or less, 0.1 mass% or less, 0.05 mass% or less, or 0.01 mass% or less.
[0026] Although it depends on the thickness of the ceramic plate, when the ceramic plate is thin (for example, about 0.3 mm), the location where the YMgSi2O5N, etc. is present can be relatively easily confirmed by irradiating light from one main surface of the ceramic plate and observing the ceramic plate from the other main surface. That is, the location where the YMgSi2O5N, etc. is present has low light transmittance, and the corresponding location is observed as black on the observation surface of the ceramic plate (the main surface opposite to the main surface irradiated with light). By observing the corresponding location preferentially, the content of the YMgSi2O5N, etc. can be easily confirmed.
[0027] The ceramic plate may have excellent insulating properties. The dielectric breakdown voltage of the ceramic plate may be, for example, 9.0 kV or more, 9.5 kV or more, or 10.0 kV or more. In this specification, the term "dielectric breakdown voltage" refers to a value measured by a voltage tester in accordance with the description of JIS C 2110-1:2016 "Solid Electrical Insulating Materials - Test Method for Dielectric Breakdown Strength". As the dielectric breakdown tester, for example, "TOS-8700" (device name) manufactured by Kikusui Electronics Co., Ltd. may be used.
[0028] The ceramic plate described above is useful as a ceramic insulating plate due to the specific composition of its main surface. The ceramic plate or insulating plate can be used as a circuit board by forming an electric circuit or the like composed of a metal layer on one or both main surfaces. The insulating plate is particularly suitable for circuit boards for inverters used in hybrid cars, electric cars, trains, industrial robots, etc.
[0029] The above-mentioned ceramic plate can be manufactured, for example, by the following method. One embodiment of the method for manufacturing the ceramic plate includes a step of heat treating a green sheet containing silicon nitride, silicon dioxide, magnesium oxide, and yttrium oxide.
[0030] The green sheet may be prepared, for example, by the following procedure. The green sheet may be obtained by compressing a mixed powder containing silicon nitride and a sintering aid and processing it into a sheet shape, or may be obtained by preparing a slurry containing silicon nitride, a sintering aid, and a solvent, or a slurry containing silicon nitride, a sintering aid, a binder, and a solvent, forming a coating film on a release film, and then peeling off the release film. For coating the slurry, for example, a doctor blade method, a calendar method, or an extrusion method can be used. When forming a green sheet using a slurry, the green sheet may be heated to reduce the content of the solvent in advance. The green sheet may be processed into a desired shape and size, for example, by cutting or the like.
[0031] The sintering aids include silicon dioxide (SiO2), magnesium oxide (MgO), and yttrium oxide (Y2O3). The sintering aids form a liquid phase at the sintering temperature. The α-silicon nitride (α-SN) dissolves in the liquid phase and is converted to β-silicon nitride (β-SN), promoting grain growth to obtain a ceramic plate.
[0032] In the above manufacturing method, the content of the silicon dioxide is 0.90 parts by mass or more based on the total amount of the green sheet. The content of the silicon dioxide may be, for example, 0.92 parts by mass or more, 0.93 parts by mass or more, or 0.95 parts by mass or more based on the total amount of the green sheet. The content of the silicon dioxide may be, for example, 1.00 parts by mass or less, 0.98 parts by mass or less, or 0.96 parts by mass or less based on the total amount of the green sheet.
[0033] The content of silicon dioxide in this specification means the total amount of silicon dioxide added as a sintering aid and silicon dioxide formed by oxidizing the surface of silicon nitride. The amount of oxygen contained in silicon nitride means the value measured by an oxygen / nitrogen analyzer in accordance with the description of JIS R 1603:2007 "Chemical analysis method of silicon nitride fine powder for fine ceramics". As the oxygen / nitrogen analyzer, for example, "EMGA-920" (instrument name) manufactured by Horiba Ltd. can be used.
[0034] In the above heat treatment, the heating rate in the temperature range below 1400°C may be adjusted as appropriate. The heating rate in the temperature range below 1400°C may be, for example, 1.5°C / min or more, or 2.0°C / min or more. When the green sheet contains a binder or the like, the heating rate in the temperature range below 1400°C is set within the above range, so that the binder in the green sheet can be sufficiently burned and the binder content can be sufficiently reduced. When the heating rate is set higher, the binder content in the green sheet may be reduced by holding the green sheet at a temperature below 1400°C for a predetermined period of time.
[0035] In the heat treatment, the green sheet is heated to 1400 to 1800° C., thereby accelerating the conversion of α-silicon nitride to β-silicon nitride in the green sheet and the grain growth of β-silicon nitride. In the above-mentioned manufacturing method, the heat treatment is performed at a temperature rise rate of 0.50° C. / min or less in a temperature range of 1400 to 1800° C.
[0036] The heating rate in the temperature range of 1400 to 1800°C may be, for example, 0.47°C / min or less, 0.46°C / min or less, or 0.45°C / min or less. By setting the heating rate within the above range, the grain growth of β-silicon nitride can be more sufficiently promoted, and a ceramic board having a denser structure can be obtained. The heating rate in the temperature range of 1400 to 1800°C may be, for example, 0.40°C / min or more, 0.42°C / min or more, or 0.43°C / min or more. By setting the heating rate within the above range, a ceramic board can be manufactured in a relatively short time, and therefore a decrease in productivity can be sufficiently suppressed. The heating rate in the temperature range of 1400 to 1800°C may be adjusted within the above range, and may be, for example, 0.40 to 0.50°C / min, 0.42 to 0.47°C / min, or 0.43 to 0.46°C / min.
[0037] The heat treatment may be carried out, for example, in a nitrogen atmosphere containing nitrogen, or in nitrogen gas.
[0038] In the above-mentioned manufacturing method, a setter may be used from the viewpoint of suppressing the ceramic plate from being burned into a sintering furnace or the like. The setter may be, for example, a commercially available sintered body, or one prepared by a known method. Examples of the setter include those composed of at least one selected from the group consisting of boron nitride, silicon carbide, alumina, zirconia, graphite, and the like. Among these, a setter composed of boron nitride is preferably used because it has heat resistance and good machinability.
[0039] In the above-mentioned manufacturing method, a plurality of green sheets may be stacked and heat-treated at the same time. In this case, a release agent may be applied to the main surface of the green sheets to suppress adhesion between the overlapping green sheets. The release agent may be, for example, a ceramic powder such as boron nitride, or a graphite powder.
[0040] In the heat treatment process, the sintering aid is exposed to high temperatures and is removed from the system. However, at least a part of the sintering aid remains in the ceramic plate as a by-product generated through side reactions such as those shown in the following reaction formulas (1) to (3). According to the inventors' investigations, when a large amount of silicon dioxide is used, reaction formula (3) tends to take precedence over reaction formula (2). Si3N4+Y2O3→Y2Si3O3N4…Reaction formula (1) Si3N4+SiO2+4Y2O3→Y8Si4N4O 14 …Reaction scheme (2) Si3N4+5SiO2+4MgO+2Y2O3→4YMgSi2O5N …Reaction formula (3)
[0041] According to the investigations of the present inventors, among the above-mentioned by-products, YMgSi2O5N, Y2Si3O3N4, and Y8Si4N4O 14 Although both are insulating, Y2Si3O3N4 and Y8Si4N4O 14 The dielectric breakdown voltage of the ceramic plate tends to be lower when YMgSi2O5N remains compared to when YMgSi2O5N remains.
[0042] Although several embodiments have been described above, the present disclosure is not limited to the above-described embodiments. In addition, the descriptions of the above-described embodiments can be mutually applied. EXAMPLES
[0043] The present disclosure will be described in more detail below with reference to examples and comparative examples. However, the present disclosure is not limited to the following examples.
[0044] Example 1 [Ceramic plate manufacturing] A mixture containing 91.4 parts by mass of silicon nitride, 1.0 part by mass of silicon dioxide (SiO2), 6.0 parts by mass of magnesium oxide (MgO), and 1.6 parts by mass of yttrium oxide (Y2O3) was prepared in a container, and the mixture was uniaxially pressurized to produce a sheet-shaped molded body. The molded body was then punched out using a cutting device to obtain 70 green sheets having a rectangular parallelepiped shape. The obtained green sheets were sandwiched between a pair of boron nitride setters (manufactured by Denka Co., Ltd., product name: NB-1000) to obtain a laminate in which two setters and 70 green sheets were stacked.
[0045] The laminate obtained as described above was placed in a sintering furnace and heat-treated under a nitrogen atmosphere to prepare a ceramic plate. The heat treatment conditions were a temperature rise rate (set value) of 0.45°C / min from 1400 to 1800°C, and a holding time of 500 minutes after reaching 1800°C. After the heat treatment, the laminate was naturally cooled to room temperature.
[0046] Example 2 A ceramic plate was prepared in the same manner as in Example 1, except that the amount of silicon dioxide was changed to 0.95 parts by mass.
[0047] Example 3 A ceramic plate was prepared in the same manner as in Example 1, except that the amount of silicon dioxide was changed to 0.90 parts by mass.
[0048] Example 4 A ceramic plate was prepared in the same manner as in Example 1, except that the heating rate was changed to 0.47° C. / min.
[0049] Example 5 A ceramic plate was prepared in the same manner as in Example 1, except that the heating rate was changed to 0.50° C. / min.
[0050] Comparative Example 1 A ceramic plate was prepared in the same manner as in Example 1, except that the amount of silicon dioxide was changed to 0.2 parts by mass.
[0051] Comparative Example 2 A ceramic plate was prepared in the same manner as in Example 1, except that the heating rate was changed to 5.0° C. / min.
[0052] [Surface composition analysis by X-ray diffraction method] The ceramic plates prepared in Examples 1 to 5 and Comparative Examples 1 and 2 were subjected to surface observation by an optical microscope and surface composition analysis by an X-ray diffraction method. The results are shown in Table 1. For reference, optical microscope photographs of a part of the surface of the ceramic plates prepared in Example 1 and Comparative Example 1 are shown in Figs. 1 and 2, respectively. These optical microscope photographs were taken when the ceramic plates were irradiated with light from the main surface opposite to the observation surface. As shown in Fig. 2, in the ceramic plate prepared in Comparative Example 1, many parts are observed as black shadows on the observation surface (the main surface opposite to the main surface irradiated with light). The area indicated by R in Fig. 2 shows an example of the observation area, and has a size of 0.6 mm x 0.9 mm.
[0053] [Table 1] [Industrial Applicability]
[0054] According to the present disclosure, it is possible to provide a ceramic board having excellent insulating properties and a method for manufacturing the same. In addition, according to the method for manufacturing a ceramic board of the present disclosure, since a sintering aid is used, it is possible to produce a ceramic substrate having excellent insulating properties with a high yield while suppressing an increase in manufacturing costs.
Claims
1. Silicon nitride, YMgSi 2 O 5 N.Y. 8 S 4 N 4 O 14 , and Y 2 S 3 O 3 N 4 A ceramic plate comprising: When quantitative analysis of the composition on the surface is performed by X-ray diffraction, the components detected are silicon nitride, the YMgSi 2 O 5 N, the Y 8 S 4 N 4 O 14 and the Y 2 S 3 O 3 N 4 and the YMgSi 2 O 5 The maximum content of N is less than 8.0 mass% based on the total amount of the components, the total content of Y 8 Si 4 N 4 O 14 and Y 2 Si 3 O 3 N 4 is less than 4.0 mass% based on the total amount of the components, 2 O 5 N, the Y 8 S 4 N 4 O 14 and the Y 2 S 3 O 3 N 4 The Y 8 S 4 N 4 O 14 and the Y 2 S 3 O 3 N 4 The ratio of the total amount of is 0.250 or more.
2. The method includes a step of heat-treating a green sheet containing silicon nitride, silicon dioxide, magnesium oxide, and yttrium oxide to obtain a ceramic plate, The content of the silicon dioxide is 0.90 parts by mass or more based on the total amount of the green sheet, The heat treatment is performed at a temperature rise rate of 0.50° C. / min or less at 1400° C. to 1800° C., When the composition of the surface of the ceramic plate is quantitatively analyzed by X-ray diffraction, the components detected are silicon nitride, YMgSi 2 O 5 N.Y. 8 S 4 N 4 O 14 , and Y 2 S 3 O 3 N 4 and the YMgSi 2 O 5 The maximum content of N is less than 8.0 mass% based on the total amount of the components, the total content of Y 8 Si 4 N 4 O 14 and Y 2 Si 3 O 3 N 4 is less than 4.0 mass% based on the total amount of the components, 2 O 5 N, the Y 8 S 4 N 4 O 14 and the Y 2 S 3 O 3 N 4 The Y 8 S 4 N 4 O 14 and the Y 2 S 3 O 3 N 4 The method for producing a ceramic plate, wherein the ratio of the total amount of is 0.250 or more.
Citation Information
Patent Citations
Silicon nitride sintered compact and its production
JP1996048564A
Self-reinforced sintered silicon nitride
JP1996510201A
Silicon nitride substrate, silicon nitride circuit substrate using the same, and its use
WO2007018050A1
Ceramic sintered compact, circuit board using the same, electronic device and thermoelectric conversion module
WO2011111746A1
Silicon nitride sintered compact, heating device and adsorption device
WO2014051088A1